2004
DOI: 10.1634/theoncologist.2004-0090
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Alfa 60,000 U Once Weekly Followed by 120,000 U Every 3 Weeks Increases and Maintains Hemoglobin Levels in Anemic Cancer Patients Undergoing Chemotherapy

Abstract: Purpose. Epoetin alfa administered s.c. three times weekly or once weekly increases hemoglobin (Hb) levels, decreases transfusion requirements, and improves quality of life in anemic cancer patients receiving chemotherapy. This study assessed the feasibility of using higher initial doses of once-weekly epoetin alfa followed by less frequent maintenance doses to increase and then maintain adequate Hb levels in this population. Materials and Methods.In this open-label, nonrandomized, pilot study, anemic (baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In one of those studies, patients whose Hb levels increased by ≥2 g/dl were placed on a maintenance dosing schedule of 120,000 U every 3 weeks. Little change in mean Hb level was observed from the end of initial therapy through the maintenance period, suggesting the benefit of higher initial qw epoetin alfa doses and less frequent dosing during maintenance [38].…”
Section: Dosingmentioning
confidence: 95%
See 1 more Smart Citation
“…In one of those studies, patients whose Hb levels increased by ≥2 g/dl were placed on a maintenance dosing schedule of 120,000 U every 3 weeks. Little change in mean Hb level was observed from the end of initial therapy through the maintenance period, suggesting the benefit of higher initial qw epoetin alfa doses and less frequent dosing during maintenance [38].…”
Section: Dosingmentioning
confidence: 95%
“…More recently, alternative dosing regimens have been investigated that may be as effective as currently utilized regimens at increasing Hb levels, decreasing transfusion needs, and improving QOL, while providing greater flexibility and convenience to patients and physicians [38,39]. In two pilot studies of patients with chemotherapy-related anemia (Hb level ≤11 g/dl), an initial epoetin alfa dose of 60,000 U qw increased Hb levels by ≥2.6 g/dl from baseline at 8 weeks [38,39]. In one of those studies, patients whose Hb levels increased by ≥2 g/dl were placed on a maintenance dosing schedule of 120,000 U every 3 weeks.…”
Section: Dosingmentioning
confidence: 99%
“…Patton et al [39], in an open-label, nonrandomized pilot study, evaluated the efficacy of epoetin alfa at a dose of 60,000 IU once weekly followed by a maintenance dose of 120,000 IU every 3 weeks. Study participants were 20 anemic cancer patients with nonmyeloid malignancies who were undergoing chemotherapy.…”
Section: Further Profiling Of Epoetin Alfa and Hb Levelsmentioning
confidence: 99%
“…52 Other benefits of epoetin alfa that are under current investigation include: treatment of anemia in patients not undergoing cancer therapy; neuroprotective effects during chemotherapy; and novel dosing strategies that could improve overall response rates and time to response. [30][31][32][33][53][54][55][56] Results of studies in these areas are reported later in this article. Epoetin beta.…”
Section: Erythropoietic Agentsmentioning
confidence: 99%
“…A proof-of-concept study was conducted in 20 anemic (Hb ≤ 11 g/dL; mean baseline Hb, 10.1 g/dL) patients with nonmyeloid malignancies receiving chemotherapy. 56 week study evaluated a 60,000 U QW initial dose of epoetin alfa SC followed by a 120,000 U every-3-week (Q3W) dose in patients whose Hb increased ≥ 2 g/dL from baseline after at least 8 weeks of QW dosing. Mean Hb increased 1.0 ± 1.1 g/dL after 4 weeks and 2.9 ± 1.9 g/dL after 8 weeks to 13.0 g/dL.…”
Section: Future Directions Emerging Dosing Strategiesmentioning
confidence: 99%